2012
DOI: 10.1021/ol3022885
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Rearrangement of N-Vinyl Nitrones: Synthesis of Spiroisoxazolines and Fluorene-Tethered Isoxazoles

Abstract: N-Vinyl nitrones derived from fluorenone have been prepared via a copper-mediated coupling between fluorenone oxime and vinyl boronic acids. These compounds undergo subsequent rearrangement and addition reactions that are distinct from the traditional [3 + 2] cycloaddition reactivity of nitrones. Thermal rearrangements of fluorenone N-vinyl nitrones give spiroisoxazolines, while treatment with alkynes provides fluorene-tethered isoxazoles. The scope and limitations of the preparation of fluorenone N-vinyl nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…[9] To improve the yield, a variety of Lewis and Brønsted acids were screened and silica gel was identified as the most effective additive to enable the formation of dihydrocarbazole 1 a in 82 % yield (entries 7-10). Although the reaction could be run at lower temperatures with longer reaction times (entries [11][12], the conversion was significantly diminished. Consequently, the optimal conditions shown in Table 1, entry 10 were selected to explore the scope of the transformation for the efficient preparation of dihydrocarbazoles from non-indole precursors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] To improve the yield, a variety of Lewis and Brønsted acids were screened and silica gel was identified as the most effective additive to enable the formation of dihydrocarbazole 1 a in 82 % yield (entries 7-10). Although the reaction could be run at lower temperatures with longer reaction times (entries [11][12], the conversion was significantly diminished. Consequently, the optimal conditions shown in Table 1, entry 10 were selected to explore the scope of the transformation for the efficient preparation of dihydrocarbazoles from non-indole precursors.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, efficient conversion of chalcone-derived nitrones 3 b-3 i to dihydrocarbazoles 1 b-1 i revealed that a variety of both electron-poor and electron-rich aryl groups are tolerated. [12] The versatility of the addition and rearrangement process for a variety of different R 1 -and R 2 functional groups demonstrates the efficacy of this method for the preparation of a diverse range of dihydrocarbazoles. Furanyl-substituted dihydrocarbazole 1 j was similarly prepared from furanyl-substituted nitrone 3 j and dienyl-and dibenzylidene acetone-derived nitrones 3 k and 3 l provided the corresponding styrenyl-substituted dihydrocarbazoles 1 k and 1 l in excellent yield (entries [10][11][12].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…[5] While testing the scope of this transformation, we observed that a,b-unsaturated N-aryl nitrones can also be prepared by the copper-mediated cross coupling of aryl boronic acids and a,b-unsaturated oximes. [5] While testing the scope of this transformation, we observed that a,b-unsaturated N-aryl nitrones can also be prepared by the copper-mediated cross coupling of aryl boronic acids and a,b-unsaturated oximes.…”
mentioning
confidence: 99%